Las tradiciones ideológicas islámicas ante el repudio. Su eficacia civil en el derecho del estado español - Pérez Álvarez, Salvador ('Ilu. Revista de Ciencias de las Religiones, 2009)
Sharia is a religious legal system that is based on the divine mandates revealed in the Quram and the Sunna as has been interpreted bu the main Islamic Schools of Law, both Sunni and Shiita. In orden to understand what is at stake, distinctions between the main Islamic traditions in this ground was one of the factors that have led to an imprecise use of terminology of the Quram which refers to the Islamic divorce, that is: the Talaq. Its confusion has also been reflected in the case law of the Spanish Supreme Court which regards to the effects of Talaq under the Spanish Civil Law. Bilateral Accord concluded betwen the Spanish Goverment and the Islamic Religious Comunities of Spain has not regulated the requirements of the recognition of the islamic divorce in our legal system. Nevertheless, whether repudiation has been made under the Civil Law of a Muslim State, it could be recognized in Sapin under the rules of procedure of the International Private Law. The main purpose of such recognition is to guarantee the basic civil rights and liberties of the woman who has been repudiated.
Keywords: Sharia; Islamic School’s of Law; Marriage Law; Islamic divorce (Talaq); Requirements; Consequences; Legal framework recognition; Spanish Civil Law